Simulation of motorcyclist's kinematics during impact with W-Beam guardrail - Biliyamin, Ibitoye Adeoye; Hamouda, Abdel Magid Salem; Wong, Shaw Voon; Radin Sohadi, Radin Umar (Elsevier, 2006)
W-Beam guardrail system has been in use as a standard for roadside safety barrier since 1950s. Recently, its safety performance standard has been upgraded to absorb impact from large vehicles. This performance standard requires guardrail system to be capable of capturing and redirecting a large range of vehicle types and sizes but its effects on safety of motorcyclists are not yet understood.